Pengaruh Pertumbuhan Ekonomi dan Ketimpangan Pendapatan terhadap Indeks Pembangunan Manusia antar Kabupaten di Provinsi Papua Tengah - Rahmat Arapi; Anjte Tuasela (STIE Jambatan Bulan, 2024)
This research aims to determine the influence of economic growth, funds and income inequality on HDI between districts in Central Papua Province. The economic growth variable is measured using ADHK GDP rate data, while income inequality is measured using the Gini Ratio. The associative method with a quantitative approach was used in this research. The data collection technique uses documentation techniques by collecting data published by the Central Statistics Agency for the years 2012-2021. The data analysis instrument used is Panel Data Regression with the help of the Eviews 10 application. The research results show that economic growth has a negative and significant effect on HDI, while income inequality has a positive and significant effect on HDI between districts in Central Papua Province.